MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PEMBELAJARAN MULTIMEDIA INTERAKTIF DENGAN MODEL DISCOVERY LEARNING - Dian Puspita Aprilia Laknasa; Abdul Wahab Abdullah; Khardiyawan A. Y. Pauweni; Kartin Usman; Abas Kaluku (Universitas Negeri Gorontalo, 2021)
The purpose of this research is to improve students’ mathematics learning outcomes on ball material through interactive multimedia learning with discovery learning models. This research was conducted in class IX-4 of MTs Negeri 2 Boalemo in the 2019/2020 school year with a total of 21 student. This research is a Classroom Action Research conducted with 1 cycle. The instruments used are in the form of teacher activity observation sheets, student activity observation sheets, and learning outcomes tests. The results of observations of teacher activities obtained a minimum category of good or very good with a percentage of 87.5% and the results of observations of student activities obtained a minimum category of good or very good with a percentage of 91%. Meanwhile, for the learning outcomes test, 19 students achieved the Minimum Completeness Criteria (KKM), or about 90.5%, and 2 students did not complete the test, or around 9.5%. The average student's mathematics learning outcomes on the ball material are 89% or meet the indicators of success